(untitled) (Research, Society and Development, 2021)
This paper describes the macroscopic, histopathological and immunohistochemical (IHC) aspects of a case of mucinous adenocarcinoma in a Chow-chow canine, with a history of vomiting and weight loss. Ultrasonographic examination revealed diffuse thickening and loss of stratification of the stomach wall suggestive of gastric neoplasia. After death, the animal was sent to the Laboratório Regional de Diagnóstico of the Faculdade de Veterinária of the Universidade Federal de Pelotas (LRD/UFPel) to establish the definitive diagnosis. At necropsy, there was diffuse thickening of the stomach wall in the anthropyloric region and the caudal portion of the body of the organ. , with flattening of the folds and ulcerations in the mucosa, in addition to enlargement of the mesenteric lymph nodes. In the histopathological evaluation of the stomach, pleomorphic epithelial cells were observed, with paracentral nuclei and abundant cytoplasm containing mucin, characterizing signet ring cells. Neoplastic cells affected all layers of the gastric wall, being also observed inside lymphatic vessels, regional lymph nodes and liver. PAS staining showed the presence of mucin in the cytoplasm of neoplastic cells. In IHC there was immunostaining of tumor cells for cytokeratin. The diagnosis of gastric mucinous adenocarcinoma in this case was based on macroscopic findings, histopathological and confirmed by IHC.